PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU PENYEBAR INFORMASI YANG MENIMBULKAN RASA KEBENCIAN, PERMUSUHAN DAN SARA BERDASARKAN UNDANG – UNDANG NOMOR 19 TAHUN 2016 PERUBAHAN ATAS UNDANG- UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - HUTAURUK, FEBRY JAYANTI; Artina, Dessy; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Indonesia is one of the many developing countries that use social media. This can be seen from the many users of communication tools that aim to make it easier for people to get information from one to the other. The condition turned out to open a lot of opportunities for parties who are not responsible for mususing social media is based on this understanding then the authors formulate two formulation of the problem namely: first, how criminal responsibility for the perpetrators of information dissemination that creates hatred, hostility and SARA based on law number 19 of 2016 amandments to law number 11 of 2008 concerning electronic information and transactions? Second, how is the ideal concept of criminal responsibility for the perpetrators of disseminating hate speech, hostility, and SARA on social media?In writing this thesis, the author uses the type of normative juridical writing that is research on the principles contained in the criminal law. This study uses secondary data anda tertiary data and data collection techniques in research with library studies.From the results of this study can be concluded first,criminal responsibility for the perpetrators of information dissemination that creates hatred, hostility and SARA based on law number 19 of 2016 amandments to law number 11 of 2008 concerning electronic information and transactions still not effective in giving punishment to the perpetrators so that there is no deterrent effect on the perpetrators who disseminate information that gives rise to hatred, hostility and SARA. Second, the ideal concept criminal responsibility towards the perpetrators hate speech, hostility, and radical intolerance and transaction law stiil has a very broad definition in terms of hate speech so that in the future it will provide good legal rules so that the criminal responsibility is fulfilled in these elements.